Review. Issue 1 (1st April 2013) - Ralph, Susie
'l'eleganza In Esilio: Tra Moda E Costume, Il Tempo Di Djagilev'/'elegance In Exile: Between Fashion And Costume In The Time Of Diaghilev', Museo Di Palazzo Mocenigo, Venice, 17 September 2011–6 January 2012